2013
DOI: 10.1007/s11096-013-9873-x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of drug label instructions: a study among four immigrants groups in the Netherlands

Abstract: Incorrect interpretation of certain drug label instructions occurred among the majority of both immigrants and natives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 15 publications
1
35
0
Order By: Relevance
“…Adequate health literacy skills are essential to understand the aim, expected (side) effects and specific instructions of drug treatment . In a previous study, we showed incorrect interpretation of commonly used drug label instructions among both immigrants and natives in the Netherlands, which might also be caused by limited health literacy skills …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Adequate health literacy skills are essential to understand the aim, expected (side) effects and specific instructions of drug treatment . In a previous study, we showed incorrect interpretation of commonly used drug label instructions among both immigrants and natives in the Netherlands, which might also be caused by limited health literacy skills …”
Section: Introductionmentioning
confidence: 84%
“…1,8,9 In a previous study, we showed incorrect interpretation of commonly used drug label instructions among both immigrants and natives in the Netherlands, which might also be caused by limited health literacy skills. 10 Furthermore, studies have shown that patients with limited health literacy skills have poor selfmanagement knowledge, resulting in lower medication adherence, poor health outcomes and increased health costs for society. 11,12 These limited health literacy skills seem to be more prevalent among elderly, ethnic minority groups and people with a lower socioeconomic status (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In another study by the same group focusing on auxiliary labels, over 90% of the patients made errors in understanding label instructions, and patients with limited literacy skills and patients on multiple drug regimens were found to make more errors . In the Netherlands, Koster et al confirmed these findings in an immigrant population with poor knowledge of Dutch and found that the instruction to use prescriptions as needed and auxiliary labels are problematic: 40% of label instructions were understood correctly . In another study, they confirmed the association between low health literacy and problems with understanding prescription labels …”
Section: Introductionmentioning
confidence: 87%
“…10 In the Netherlands, Koster et al confirmed these findings in an immigrant population with poor knowledge of Dutch and found that the instruction to use prescriptions as needed and auxiliary labels are problematic: 40% of label instructions were understood correctly. 11 In another study, they confirmed the association between low health literacy and problems with understanding prescription labels. 12 There are several reasons that contribute to poor understanding of label instructions, including the design of the prescription label, lack of coherency in information, and the text of the dosing instructions itself.…”
mentioning
confidence: 82%
“…Globally, 50% of adults have been reported to have misunderstood medication instructions which could be the cause of not using medication as prescribed [2]. Muhammed, Jibril, and Dauda [3] recommend that patients should be encouraged to comply with their prescribed medications through educational and training programs.…”
Section: Introductionmentioning
confidence: 99%